Larvicidal activities of mentha piperita (peppermint) essential oil against aedes albopictus / Nur Alia Jamanhuri - Jamanhuri, Nur Alia (2019)
Dengue is a mosquito-borne viral-borne disease that is transmitted by female Aedes mosquitoes. The excessive use of synthetic insecticides has caused the evolution, development and spread of insecticide resistance in dengue vectors including Aedes albopictus. This can be tackled using alternative methods of mosquito control based on botanical products such as Mentha piperita (peppermint). The rationale of this study was to determine the efficacy of Mentha piperita as an organic larvicide by evaluating the mortality rate and lethal concentration (LC₅₀ and LC₉₀ ) of its essential oil against Aedes albopictus. Mosquitoes were reared in an insectary and larvae at 3rd instar were used. Essential oil was obtained using hydro-distillation method with a Clevenger apparatus and acetone as a solvent. The mortality rate was determined following 24 and 48 hours’ exposure to 5 different test concentrations (100, 150, 200, 250 and 300 ppm) alongside 10% (v/v) of acetone (quality control), temephos (positive control) and distilled water (negative control). Data was analyzed using Probit analysis and analysis of variance (ANOVA). The highest mortality rates achieved was 93% when exposed to 250 ppm concentration of essential oil. LC₅₀ and LC₉₀ values were observed at 177.243 ppm and 290.363 ppm respectively. The results showed significant differences from the values obtained (p = 0.000). Findings from this study concludes the potential of Mentha piperita essential oil as an efficient larvicide agent. Further isolation and purification of phytochemical compounds is warranted to determine the bioactive compounds responsible for its bioactivity.